2013
DOI: 10.5194/bg-10-7817-2013
|View full text |Cite
|
Sign up to set email alerts
|

Ocean acidification from 1997 to 2011 in the subarctic western North Pacific Ocean

Abstract: Abstract. Rising atmospheric CO 2 contents have led to greater CO 2 uptake by the oceans, lowering both pH due to increasing hydrogen ions and CaCO 3 saturation states due to declining carbonate ion (CO 2− 3 ). Here we used previously compiled data sets and new data collected in 2010 and 2011 to investigate ocean acidification of the North Pacific western subarctic gyre. In winter, the western subarctic gyre is a source of CO 2 to the atmosphere because of convective mixing of deep waters rich in dissolved ino… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 42 publications
(83 reference statements)
4
33
1
Order By: Relevance
“…The results of the decomposition of ΔΩ arg were similar to those for ΔΩ cal (Figure 6, blue 47°N, 160°E), Wakita et al [2013] reported rates of À0.0055 a À1 to À0.0077 a À1 and À0.0035 a À1 to À0.0048 a À1 for Ω cal and Ω arg , respectively. Using repeat hydrography data, Murata and Saito [2012] found a maximum rate of Ω arg decrease of 0.034 a À1 at 200-300 dbar at 20°N along the 179°E meridian.…”
Section: 1002/2014gb004908supporting
confidence: 69%
“…The results of the decomposition of ΔΩ arg were similar to those for ΔΩ cal (Figure 6, blue 47°N, 160°E), Wakita et al [2013] reported rates of À0.0055 a À1 to À0.0077 a À1 and À0.0035 a À1 to À0.0048 a À1 for Ω cal and Ω arg , respectively. Using repeat hydrography data, Murata and Saito [2012] found a maximum rate of Ω arg decrease of 0.034 a À1 at 200-300 dbar at 20°N along the 179°E meridian.…”
Section: 1002/2014gb004908supporting
confidence: 69%
“…A detailed and long-term observation in the subtropical North Pacific off the southern coast of Japan showed that Ωar of surface water is ~3.5 during the summer, but decreases to lower than 3.0 during the winter (at 33°40′N-34°00′N; Ishii et al (2011)). In the western subarctic gyre further north, a similar seasonal pattern in surface Ωar was observed, but with a larger variation and lower values for both summer (~2.5) and winter (~1.3) (at ~45°N; Wakita et al 2013). From these observations, the Ωar of waters in Tokyo Bay would be ~3 with a maximum value in summer, if there is no alternation of water properties by processes within the bay.…”
Section: Study Areasupporting
confidence: 56%
“…Ishii et al 2011;Wakita et al 2013). The very high primary production and resulting remineralization of organic matter in this shallow and eutrophicated bay are the major causes of such large variations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calculated pH trends for the North Atlantic Gyre suggest a decrease of −0.0022 ± 0.0004 units yr −1 over the period 1981-2007(Lauvset and Gruber, 2014. In the North Pacific, a pH decrease of −0.0011 ± 0.0004 units yr −1 from 1997 to 2011 has been calculated ( Table 3; Wakita et al, 2013).…”
Section: Updates To Ar5mentioning
confidence: 92%